Investigation of the Relationship between Sensory-Processing Skills and Motor Functions in Children with Cerebral Palsy - Serhat Erkek; Çiğdem Çekmece (MDPI AG, 2023)
The main purpose of this study is to examine the relationship between sensory-processing skills and gross motor functions, bimanual motor functions, and balance in children with cerebral palsy (CP). A total of 47 patients between the ages of 3 and 10, diagnosed with CP, who received or applied for treatment in our physical therapy and rehabilitation unit were included in the study. Sensory profiling (SP), assisting hand assessment (AHA), the Gross Motor Function Measure-66 (GMFM-66), and the Pediatric Berg Balance Scale (PBBS) were used in the evaluation of the children with CP who participated in the study. The Gross Motor Function Classification System (GMFCS) was used to classify the children based on functional abilities and limitations, and the Manual Ability Classification System (MACS) was used to classify the children based on manual dexterity. The SP parameters were compared with AHA, GMFM-66, and PBBS results, and with GMFCS and MACS levels. Statistically significant relationships were found between AHA and SP, PBBS, and SP and between GMFM-66 and SP (p < 0.05). Our study shows that there are some disorders in sensory processing in children with CP. We think that sensory evaluations should be included in the CP rehabilitation program.